2008 Global Hunger Index: The challenge of hunger - von Grebmer, Klaus; Fritschel, Heidi; Nestorova, Bella; Olofinbiyi, Tolulope; Pandya-Lorch, Rajul; Yohannes, Yisehac (International Food Policy Research Institute, 2008)
The 2008 Global Hunger Index (GHI) shows that the world has made slow progress in reducing food insecurity since 1990, with dramatic differences among regions and countries. In the nearly two decades since 1990, some regions - South and Southeast Asia, the Near East and North Africa, and Latin America and the Caribbean - have made significant headway in improving food security. Nevertheless, the GHI remains high in South Asia. The GHI is similarly high in Sub-Saharan Africa, where progress has been marginal since 1990. The GHI level in the world as a whole remains serious. The countries with the most worrisome hunger status and the highest 2008 GHI scores are predominantly in Sub-Saharan Africa, with the Democratic Republic of Congo, Eritrea, Burundi, Niger, and Sierra Leone at the bottom of the list. Several dozen countries in various regions have GHI scores categorized as low. Hunger is closely tied to poverty, and countries with high levels of hunger are overwhelmingly low- or low-middle-income countries. Sub-Saharan Africa and South Asia are the regions with the highest GHI scores and the highest poverty rates. The recent advent of higher food prices has uneven effects across countries, depending on a range of factors, including whether countries are net importers or exporters of food. Among the countries for which the GHI is calculated, net cereal importers, for example, greatly outnumber exporters, implying that many more countries combating hunger are likely to suffer from higher prices than benefit from them. Higher food prices have also caused violent and nonviolent protests in dozens of countries. In this context of higher food prices, prospects for improving food and nutrition security do not appear favorable, given that at least 800 million people were food insecure even before the food price crisis hit. Higher food prices cut into poor households' food budgets, with particularly serious risks for undernourished infants and children. High prices also reduce the amount of food aid that donors can supply with a given amount of funds.